Late‐Quaternary miliolite (biogenic carbonate) deposits and their implications for sea‐level fluctuations and climatic variability. Issue 5 (13th February 2021) - Durga Prasad, A.; Bhattacharya, Falguni; Chauhan, Gaurav; Balaji, D.; Thakkar, M.G.; Rao, Y. Srinivasa
Abstract: The western coast of India (Kachchh) has ubiquitous preservations of Quaternary carbonate deposits popularly known as "miliolites". Field‐based detail documentation of the nature and distribution of miliolites supported by sedimentology and scanning electron microscopy (SEM) microtextural studies indicates that the miliolites were primarily deposited by wind as aeolinites and are termed "primary miliolites (PM)". These were subsequently fluvially eroded and deposited and such deposits are termed "secondary miliolites (SM)". The PM are dated between 28 ka to 16 ka largely clustering around the Last Glacial Maxima (LGM). In comparison, the fluvially reworked SM occurs as valley‐fill deposits and were deposited episodically during 23 ka to 10 ka before present. Climatically, the deposition of PMs suggests enhanced aridity whereas SMs represent episodic strengthening of the Indian Summer Monsoon (ISM). The bedding attitudes of the PMs indicate that they were deposited predominantly by the northeasterly winds whereas the presence of the deflation lag deposits suggests downwind migration of sands during the equilibrium condition (reduced sediment supply). The aeolian parameters (based on the grain size and wind velocities) for PMs indicate high shear velocity ( 23 to 48 cm −1 ) and high transport rate (< 0.1 to 0.2 g/cm s). The short average flying distance implies that the biogenic sands were transported in multiple pulses (from coast to inland) at rates varying from 200 m/h to 1 km/h. Comparing our data with related occurrences along the biologically productive coasts in the mid‐latitudinal belt indicates that the regional/global aridity during the lowered sea level was responsible for inland occurrences of aeolinites, particularly during the LGM. The strengthened northeast monsoon winds during the LGM was conducive to upwelling and production of biogenic carbonates along the coasts. The subsequent reworking of the aeolinites were mainly the results of local variability in precipitation. Abstract : (A) Comparing our data of miliolites with that of Global distribution of aeolianites along the mid‐latitudinal coasts indicates that regional/global aridity in association with the lowered sea level along the biologically productive coasts led to the deposition of aeolianites particularly during the LGM. (B) The timeframe of deposition of aeolian miliolites in Kachchh between the MIS‐2 to MIS‐1 is associated with the less humid period of northwest Africa. The period witnessed the bloom in the occurrences of the benthic foraminifera (C. wuellerstorfi ) along the African coast and also the lower values of δ 18 O from the ice core records that represents cold tropical climate in Qinghhai –Tibetan plateau region. Also, higher values of δ 18 O from the N. Dutertrei foraminiferal assemblages are reflected during the period in the Arabian sea. The shaded part represents the timeframe of the present study (C) In the Indian Ocean, the period between MIS‐2 to MIS‐1 that marks the LGM indicates lower values of foraminiferal trace elements as indicated by the ratios of Ba/Ca and Mg/Ca ratios‐proxies for past river run‐offs and past sea‐surface temperatures. In the Arabian‐sea, this phase is marked by high dolomite concentration and higher values of δ 18 O from the G. ruber . An increase in the biological productivity has been shown after the LGM which is indicative of the strengthening of moisture laden winds (ISM). The maximum lowering of the sea‐level during the LGM (shown by the purple bar) that marks the major deposition of the primary miliolites also correlates with lowered Ba/Ca and Mg/Ca ratios‐proxies in the Indian ocean and higher dolomite concentration and higher values of δ 18 O from the G. ruber (D) The occurrences of miliolites deposition observed in Saurashtra, western coast (1) since 80 ka is categorized into marine, aeolian and fluvial. Similar occurrences of aeolinites are observed from southern coast of India and China (2), Mediterranean (3), Australia (4), Pacific Islands and North America (5), Atlantic Ocean (6) (E) Deposition of miliolites in Saurashtra and Kachchh since 30 ka. Miliolites in Saurashtra are categorized into marine, aeolian and fluvial. Miliolites in Kachchh are categorized into aeolian (PM) and fluvial (SM). Migration of miliolitic sand grains is shown in time‐1 (erosion) and time‐2 (deposition).